Surgical Exposure of Bilateral Palatally Impacted Upper Canines and Its Proper Alignment with Fixed Appliance in the Dental Arch - A Case Report (Bangladesh Journal of Orthodontics and Dentofacial Orthopedics, 2013)
A case of impacted upper canines of 18 years is presented. Any deviation from the normal sequence of development leads to the impaction of teeth. Although the best treatment alternative for impacted teeth is extraction, the same cannot be directly applied to canines. Since canines present with a high demand on aesthetic and functional requirements, alignment of impacted canines into the arch is the best treatment approach. In the present case, a fixed appliance mechanotherapy was used to bring the impacted canines into occlusion. Total treatment time was about 18 months. Post-treatment records demonstrated good vitality of the impacted tooth and the adjacent teeth. DOI: http://dx.doi.org/10.3329/bjodfo.v1i2.15985 Ban J Orthod & Dentofac Orthop, April 2011; Vol-1, No.2, 13-15